2022
DOI: 10.1039/d2sm00198e
|View full text |Cite
|
Sign up to set email alerts
|

Micrometer-size double-helical structures from phospholipid-modified carbon nanotubes

Abstract: Biomolecular self-assembly plays a key role in the life system. Herein the double-helical phospholipid modified carbon nanotubes structures, first order, and secondary helical hybrids were constructed using self-assembly of phospholipids...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Transmission electron microscopy experiments have shown that single-tailed phospholipids form supramolecular complexes on the surface of CNTs [ 10 , 15 ]. Recently, self-assembly of phospholipids on CNTs has been shown to result in the formation of double-helical phospholipid-modified nanotube structures [ 16 , 17 ]. Such experimental findings are remarkable in view of the types of structures formed on the surface of CNTs and the potential applications of lipid–CNT hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission electron microscopy experiments have shown that single-tailed phospholipids form supramolecular complexes on the surface of CNTs [ 10 , 15 ]. Recently, self-assembly of phospholipids on CNTs has been shown to result in the formation of double-helical phospholipid-modified nanotube structures [ 16 , 17 ]. Such experimental findings are remarkable in view of the types of structures formed on the surface of CNTs and the potential applications of lipid–CNT hybrids.…”
Section: Introductionmentioning
confidence: 99%